Hubungan Tingkat Pendidikan dan Tingkat Pengetahuan tentang Merokok dengan Derajat Berat Merokok - Kusumawardhani, Arti Tyagita; Reviono, .; Prasetyawati, Arsita Eka (Nexus Kedokteran Komunitas, 2013)
Background: Smoking behavior is one of the most widely spread health problem. Oneâs smoking behavior is very much determined by oneâs knowledge of smoking behavior, where as such knowledge is also very much affected by oneâs level of education. This research aims to determine the correlation between educational level and knowledge of smoking behavior to the severity of smoking habit. Methods: This researchÂ  is an observational analysis using cross-sectional. The study was conducted in Faculty of Medicine, Sebelas Maret University. The sampleÂ  was taken using Stratified Random Sampling and Quota Sampling. Approach with male smokers administration staffs, temporary employees, lecturers, and Faculty of Medicine of Sebelas Maret University class 2011, qualifying and disqualifying with inclusion criteria. Data retrieval is done by looking at the patientâs questionnaires. Data were analyzed using correlative non-parametric Spearman analysis method, with SPSS 17.00 for Windows. Results: There is a positive correlation between oneâs educational level and the severity of oneâs smoking habit, with correlation coefficientÂ value as much asÂ 0.165Â and significance valueÂ (2-tailed)Â as much asÂ 0.208. This findings show that there is a weak and insignificant relation between both variables. Moreover, there is a weak negative correlation between oneâs educational level and oneâs knowledge on smoking habit, with significance valueÂ (2-tailed)Â as much as 0.522 and correlation coefficient value as much as 0.078. there is also a negative correlation between oneâs knowledge of smoking habit and the severity of oneâs smoking habit, with significance value(2-tailed)Â as much as 0.589 and correlation coefficient value as much as 0.071. Conclusions: There is not any significant relation between oneâs educational level and knowledge on smoking behavior to the severity of oneâs smoking habit. Keywords: Educational level, knowledge of smoking behavior, severity of smoking habit, smoking.